Strategi Marketing Public Relations Crayoone Event Organizer - Affan Ibrahim Puspateja; Siska Yuningsih (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This research is motivated by the competition for school yearbooks in high schools, junior high schools, elementary schools and equivalent in the Jakarta area and its surroundings which is quite tight. In this tight competition, a strategy is needed to promote Crayoone Event Organizer to become the best School Yearbook Company. This research was conducted in Central Jakarta.This research aims to find out what Crayoone Event Organizer does in its Marketing Public Relations strategy, find out Pull, Push and Pass Strategy, and find out the opportunities and obstacles to its Marketing Public Relations strategy. This research was conducted based on the theory of Thomas L Harris, Three Ways Strategies namely Pull, Push and Pass Strategy.This research method uses descriptive analysis with a qualitative approach. The data collection techniques used in this study were interviews, observation and documentation. The research results show that the push strategy is the main strategy used by Crayoone, by dividing marketer areas and aiming to be invited for presentations. The provision of incentives per collaboration and annual accumulative is carried out by the Crayoone Event Organizer. A pull strategy is also being pursued through social media to attract consumers via Tiktok and Instagram. The pass strategy used is sponsorship for student and non-student activities. The opportunity to carry out this strategy is better known through social media, and it is easier to convince potential service users. Distance barriers in terms of production outside the work area.